The Virtual-Representational-Abstract Framework to Support Students With Disabilities in Mathematics. (January 2019) - Bouck, Emily C.; Sprick, Jessica
The virtual-representational-abstract (VRA) framework adapts an evidence-based practice, the concrete-representational-abstract (CRA) framework, while trying to meet students and teachers where they are in terms of technology interest and use in education. This article discusses the VRA framework and the advantages of virtual manipulatives, and explains how a teacher can implement the VRA framework. Although more research is needed on the VRA framework, the VRA provides teachers an option as an instructional practice or intervention to support students struggling in mathematics.